Pemahaman Peraturan Perpajakan, Tingkat Penghasilan, Sanksi Pajak dan Kepatuhan Wajib Pajak Orang Pribadi - Utami, Ni Luh Putu Priska Sri; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2023)
The research aims to examine the effect of understanding tax regulations, income levels, and tax sanctions on individual taxpayer compliance. This research was conducted at KPP Pratama Tabanan. Data was collected in this study using a questionnaire and then disseminated in a hybrid way through survey methods. The sample is determined by nonprobability sampling technique using the accidental sampling method, with calculations using the slovin formula. This study uses multiple linear regression analysis. The results of the study prove that knowledge of tax laws, income levels, and tax sanctions contributes to individual taxpayer compliance. The implications of this research are able to explain the theoretical model of research variable values. The results of the theoretical model explain that the aspects that affect individual taxpayer compliance are caused by an understanding of tax regulations, income levels, and tax sanctions. Keywords: Compliance; Tax Regulations; Income; and Sanctions